MAN’S ROLE DEGRADATION IN SAM MENDEZ’S “AMERICAN BEAUTY” (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2012)
The objective of the study is to identify Men’s role degradation in Sam Mendez’s movie American Beauty, how men’s role degradation was described, the causes and the effects of men’s role degradation in Sam Mendez’s movie. This study uses gender role theory and social psychology approach to answer the question. I use qualitative descriptive method to gain the validity and prove the writer’s assumption. The data that found in the film are in form of sentences, phrases, dialogues, action, and mimic of the character shown in the scene. In gathering the data, I took four steps; namely, identifying, inventorying, classifying, and selecting data. First, I watched the movie and read the scripts of film. Second, I inventoried the data, classified the data, and selected the data to answer the problems. The last, the data selected are interpreted based on its function to the topic. From this study I conclude that man’s role degradation that described in American Beauty movie is about a man who faced the degradation of men’s role and men’s authority as a father and husband in the family. The causes are loss spirit of life, loss his confidence, changing gender roles, and economic changes. Beside that, the effects are not harmony relationship among the family and an affair in their marriage life.